Sentinels of inequity: examining policy requirements for equity-oriented primary healthcare - Josée G. Lavoie; Colleen Varcoe; C. Nadine Wathen; Marilyn Ford-Gilboe; Annette J. Browne; On behalf of the EQUIP Research Team (BMC, 2018)
Abstract Background Non-government, not-for-profit community health centres (CHCs) play a crucial role within healthcare systems in fostering equity, acting both as direct providers of services and as sentinels of health and social inequity. In a study of an intervention to promote equity-oriented health care, we enlisted four diverse primary healthcare clinics with mandates to serve highly marginalized populations. All of these CHCs operate as not-for-profit, non-government organizations (NGOs), and have a marginal relationship financially and socially to other parts of the system. The purpose of this paper is to provide an analysis of the factors that shape how CHCs are able to carry out an equity mandate and, from this, to identify what is required at the level of policy to enhance capacity to provide equity-oriented health care. Methods We systematically examined the clinics' policy and funding contexts, and identified influences on the clinics' capacities to promote equity-oriented health care. Results We identified three key mechanisms of influence, each playing out against the backdrop of a contested and marginal position of CHCs within the health care system: a) accountability and performance frameworks; b) patterns of funding and allocation of resources, and c) pathways for emergent priorities. We examine these mechanisms, considering how each influenced the pursuit of equity, and propose policy directions to optimize the primary health care sectors' capacity to support equity-oriented health care. Conclusions Although this analysis is based on a study within a high-income country, we argue that because the dynamics between community health centres and broader healthcare systems are similar across national boundaries, the implications have applicability to low and middle-income countries.